Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2224/sbp.2011.39.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Children who work in the street in Izmir, Turkey

Abstract: Using Izmir, Turkey as a case study the risk factors leading children to work in the streets were identified. Participants in the study were 226 children working in the streets, average age 10.35±2.21 who worked 6.8±2.11 hours per day. The great majority of the children were boys (90.2%), 77.9% were of primary school age; two-thirds of the children were working to provide an economic contribution to the family; 86.6% were from a large family; 78.8% were from a family that migrated to a big city. Almost all did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Similar to studies in other developing countries, such as Bangladesh (Salmon, 2005) and Ecuador (Lopez-Acevedo, 2002), boys are more likely to work than girls in Turkey (Karatay, 2000; Yılmaz and Dülgerler, 2011). Of the 226 children working on the street in Yılmaz and Dülgerler’s study (2011), 90% were boys. In Kıral and Tıraş ’s (2013) urban sample of “Working Child 2006”, 73% of working children between the ages six and 17 were male.…”
Section: Child Characteristicssupporting
confidence: 64%
See 2 more Smart Citations
“…Similar to studies in other developing countries, such as Bangladesh (Salmon, 2005) and Ecuador (Lopez-Acevedo, 2002), boys are more likely to work than girls in Turkey (Karatay, 2000; Yılmaz and Dülgerler, 2011). Of the 226 children working on the street in Yılmaz and Dülgerler’s study (2011), 90% were boys. In Kıral and Tıraş ’s (2013) urban sample of “Working Child 2006”, 73% of working children between the ages six and 17 were male.…”
Section: Child Characteristicssupporting
confidence: 64%
“…Various studies found that boys were more likely than girls to start working when their fathers’ employment prospects were poor (Dayıoğlu, 2006; Yılmaz and Dülgerler, 2011). However, the findings in this study were different, adding nuances to the understanding of the relationship between gender and child labor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, men who were episodic drinkers were more likely to report alcohol-related physical abuse, psychological harm and neglect of children than current abstainers (Esser et al, 2017). Qualitative research has also described how a father's alcohol use was identified as a cause of children running away and using inhalants in India (Praharaj, Verma, & Arora, 2008), and paternal drinking was linked to children living on the streets of Izmir, Turkey (Yilmaz & Dulgerler, 2011). In Ghana, care of children was compromised by the heavy drinking of both male and female caregivers (Yarney, Mba, & Asampong, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated the relationship between child labor and various demographic characteristics of both children and families, including gender, age, child birth order, parental education level, and household size (e.g., Acar 2010;Acaroğlu 2010;Akşit et al 2001;Dayıoğlu 2006;Kıral and Tıras 2013;Yılmaz and Dülgerler 2011). However, little is known about parental ethnotheories on child labor.…”
mentioning
confidence: 99%